Insights into urinary catheter colonisation and polymicrobial biofilms of Candida- bacteria under flow condition - Purvi Joshi; Rohit Bhattacharjee; Muskan Sahu; Devarshi Gajjar (Scientific Reports)
Abstract Most hospital-acquired urinary tract infections are the result of implanted urinary catheter, with majority of studies focused on a single species colonisation, but recently polymicrobial colonisations are being reported. In this study, indwelling urinary catheters were collected from ICU patients and the colonising microbiome was isolated and identified by the traditional; culturing method and metagenomics. It was observed that majority of catheters were colonised by polymicrobial biofilms, containing both bacterial and fungal isolates making them diverse and complex. However, the metagenomics results were quite surprising showing the presence of multiple organisms of which only 1or 2 showed growth when cultured. Later, in vitro assays were performed by selecting 6 combinations, with each combination containing one Candida spp. – C. albicans or C. tropicalis with one bacteria K. pneumoniae, P. aeruginosa or E. coli. It was observed that polymicrobial biofilms were stronger than mono-microbial biofilms, suggesting their increased surface adhesion. Furthermore, to simulate the dynamic environment in which cells are exposed to a certain level of fluid movement, a flow system was established to imitate the flow generated in colonized urinary catheter. We have observed changes in biofilm architecture, adhesion and thickness under flow conditions compared with static conditions, with a uniformly adhered biofilm with increased thickness of polymicrobial biofilms as compared to mono-species biofilms. The biofilm formed under flow was more viable than the static biofilm with higher number of live cells in flow condition.